Polypharmacy in Osteoporosis Patients - Yavuz Ali Karahan; Aynur Başaran; Banu Ordahan; Pelin Yıldırım; Seher Küçüksaraç; Süleyman Oktar; Neslihan Soran; Gözde Türkoğlu; Levent Tekin; Savaş Karpuz (Galenos Yayinevi, 2015)
Objective: In this study, it was aimed to determine the rates of multiple drug use in the patients with osteoporosis as well as the use of drugs affecting bone metabolism and balance. Materials and Methods: We included outpatients from Physical Medicine and Rehabilitation Policlinics diagnosed with primary or secondary osteoporosis between January 2014 and May 2014. Written consent of the participants was obtained. Data of the first 1000 patients who agreed to participate in the study were evaluated. Data regarding age, history, drugs currently being used and newly initiated were recorded. The drugs that affect bone metabolism were determined. The drugs that heva side effects including dizziness, somnolence, distractibility, decrease in the visual acuity, orthostatic hypotension and ototoxicity and were recorded because these can cause a balance disorder. Results: In this study, 64% of the participants were on five or more drugs. The most commonly used drugs were analgesics (65.4%), antihypertensives (52.6%), and drugs for digestive system (37.3%). We found that 65.5% of the participants were using drugs that may have side effects on bone metabolism and 93.7% were using drugs that may have side effects on balance. Conclusion: Multi-drug use and drug interactions should be considered during the treatment of osteoporosis and the drugs used should be recorded. Drugs that affect bone metabolism should only be used over the short term. Also, patients should be informed about side effects that might affect visuality, somatosensorial system and vestibular system and their daily activities should be regulated. (Turkish Journal of Osteoporosis 2015;21: 5-9)